Early Postnatal Care Service Utilization and Its Determinants among Women Who Gave Birth in the Last 6 Months in Wonago District, South Ethiopia: A Community-Based Cross-Sectional Study - Yordanos Tefera; Samirawit Hailu; Ruth Tilahun (Obstetrics and Gynecology International)
Background. Postnatal care is one of the key strategies to reduce maternal and newborn morbidity and mortality. Early postnatal visit is especially the most critical time for survival of mothers and newborns, particularly through early detection and management of postpartum complication. Despite the benefits, most mothers and newborns do not receive postnatal care services from health care providers during the critical first few days after delivery. Objective. The aim of this study was to assess utilization of early postnatal care service and associated factors among women who gave birth in the last six months in Wonago District, Gedeo Zone, Southern Ethiopia. Methods. A community-based cross-sectional study design was employed at Wonago District. A total of 612 mothers who gave birth in the last six months were selected by simple random sampling technique. Pretested structured questionnaire was used for data collection. Data were entered into EpiData version 3.1 and then exported into SPSS version 20 for analysis. Principal component analysis (PCA) and bivariate and multivariate logistic regression were used. Result. In this study, 13.7% of mothers utilized early postnatal care. Educational status of mothers (AOR = 3.7 : 95 CI; 1.3–10.7), place of delivery (AOR: 1.8 : 95 CI; 1.03–3.2), ANC attendance (AOR = 3.4 : 95 CI; 1.1–10.09), development of complication after delivery (AOR: 7.8 : 95 CI; 3.7–16.2), and previous history of postnatal care utilization (AOR: 2.1 : 95 CI; 1.13–3.9) were found to be associated with early postnatal care service utilization. Conclusion and Recommendations. Educational status of mothers, ANC attendance, place of delivery, delivery complication while giving recent birth, and past history of postnatal care utilization were significant predictors for early postnatal care utilization. Considering this, empowering women with education and overall strengthening of health facility to improve maternal health service utilization are necessary measures to be done at different levels to enhance early postnatal care utilization during this critical time.